The impact of Hadith perception on disputes between ahl al-Sunnah and al-Shriah al-Imamiyyah al-Ithna 'Ashariyyah - Demirel, Serdar (IIUM Press, 2011)
One of the main reasons for the controversies among legal schools in Islam revolves around the methodology of distinguishing authentic ahadith from those of rejected ones and applying the acceptable ahadith to different cases. This article studies ahadith perception in the light of this methodology to reveal the nature of disputes between ahl al-Sunnah and al-Shariah al- Imamiyyah al-Ithna 'Ashariyyah which is the biggest madhhab (school) among other madhahib apart from the ahl al-Sunnah. The disagreements among the madhhab of the ahl al-Sunnah are confined to al-furu' (applications related to secondary issues), whereas the disputes between the Sunni and the Shi'ah schools are based on both al-usul (principles) and al-furu'. The main ground for this difference is their perception of ahadith. If this fact is overlooked, the differences between the two schools cannot be grasped appropriately.